Pengaruh Penerapan Gaya Mengajar Resiprokal Terhadap Penguasaan Gerak Dasar Pada Kopstand dalam Senam Lantai pada Peserta Didik Kelas XI SMK Negeri 1 Tomohon - Marcelino R.A Tongkasi; J.J. Mangindaan; Djajati. M. Lolowang (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
The problem in this study is that students of class XI SMK Negeri 1 Tomohon do not get learning guidelines, namely task cards containing basic motion concepts on the kopstand in floor gymnastics. Students lack the opportunity to learn in the realm of knowledge and movement skills; namely the absence of interaction (feedback) as observers and performers of motion in the learning process of basic movements on the kopstand in floor gymnastics. The research method used in this research is the experimental method, the research design used is “Pre-test and post-test randomized control group design”. The population in this study were students of class XI SMK Negeri 1 Tomohon, totaling 194 students. The sample in this study amounted to 40 students. The instrument used was “basic movement ability test on kopstand in floor gymnastics”. The data obtained were tested with the t test with a confidence level of α = 0.05. The conclusions in this study are: tcount = 8.7049 > ttable = 2.0243. Based on the testing criteria, if the tcount is greater than the ttable (tcount> ttable), then H0 is rejected, which means HA is accepted so that “The application of the reciprocal teaching style has a significant effect on increasing mastery of basic movements on the kopstand in floor gymnastics in class XI students of SMK Negeri 1 Tomohon”.